Inhaled budesonide and pulmonary sarcoidosis revisited - Selroos, Olof; Brattsand, Ralph (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2024)
Results of a few controlled clinical studies have been reported with inhaled corticosteroids (ICS) in patients with pulmonary sarcoidosis. Some evidence of efficacy has been observed, but mainly with the ICS budesonide (BUD). These clinically important and statistically significant results are restricted to maintenance therapy with BUD after induction of treatment with systemic corticosteroids for a few weeks or months.  Positive results have also been described in patients with relapses after earlier treatment with oral corticosteroids. A possible explanation for BUD’s efficacy in patients with parenchymal lesions could be that inhaled BUD is rapidly absorbed into systemic circulation, creating plasma peaks which result in systemic anti-inflammatory activity in both peripheral airways and lung tissue.  At airway level this steroid activity is furthermore prolonged because a BUD fraction is intracellularly, reversibly transformed into lipophilic BUD-oleate. These mechanisms have been proposed to explain the theoretically unexpected similar efficacy of BUD compared with more lipophilic ICSs in patients with asthma and COPD. In this review we summarize the results of clinical studies with ICSs in patients with pulmonary sarcoidosis. It is obvious that current ICSs, including BUD, cannot generally be recommended as such for treatment of sarcoidosis. However, using BUD as a model substance further pharmacologic and kinetic studies could possibly define a kinetic profile giving optimal partitioning between airway and systemic activity with less adverse systemic risks. Such a substance could replace or reduce oral corticosteroids in the treatment of airway and pulmonary parenchymal diseases.